In situ quantification of HER2–protein tyrosine kinase 6 (PTK6) protein–protein complexes in paraffin sections from breast cancer tissues - Aubele, M (Nature Publishing Group, 2010)
BACKGROUND: Protein tyrosine kinase 6 (PTK6; breast tumour kinase) is overexpressed in up to 86% of the invasive breast cancers, and its association with the oncoprotein human epidermal growth factor receptor 2 (HER2) was shown in vitro by co-precipitation. Furthermore, expression of PTK6 in tumours is linked with the expression of HER2. METHOD AND RESULTS: In this study, we used the proximity ligation assay (PLA) technique on formalin-fixed paraffin sections from eighty invasive breast carcinoma tissue specimens to locate PTK6–HER2 protein–protein complexes. Proximity ligation assay signals from protein complexes were assessed quantitatively, and expression levels showed a statistically significant association with tumour size (P=0.015) and course of the cancer disease (P=0.012). CONCLUSION: Protein tyrosine kinase 6 forms protein complexes with HER2 in primary breast cancer tissues, which can be visualised by use of the PLA technique. Human epidermal growth factor receptor 2–PTK6 complexes are of prognostic relevance.